Optimal placement of Web proxies in the Internet with link capacity constraints - Tenzakhti, F. (Journal of Digital Information Management, 2006)
This paper considers the problem of placing a fixed number of proxies in the Web modelled as a tree network. The study assumes that each link in the network has a fixed capacity, and that the total load passing through a link cannot exceed this capacity. We are interested in finding a minimum cost replication set that optimises the cost of servicing access requests in a read-only environment taking into account the capacity constraints of the links.
Keywords: Dynamic programming; Link capacity; Replication; Tree network; Web server